The philosophy and practice of medicine and bioethics a naturalistic-humanistic approach - Maier, Barbara (Springer eBooks., 2011)
This book explores currently unchallenged methods in medicine, such as 'evidence-based medicine', from the perspectives of humanism and philosophy of medicine. The book discusses issues of medical treatment and moral approaches and indicates the strongest arguments. These arguments are subsequently subjected to critical analysis. The book includes new ways of thinking and explains, uses and exemplifies the 'metaphorical method'. The book argues that decision-making in medicine is inadequate unless grounded on a philosophy of medicine. As part of its argumentation, the book explores the insights offered by practical and humanistic philosophy and by creative and critical thinkers who are working on topics relevant to medicine. From this, a new and necessary definition of philosophy of life emerges: a good lifestyle no longer simply means getting physical exercise and abstaining from cigarettes and alcohol; it also means living a holistic life including all of one?s thinking, personality and actions.